Analysis of Factors Affecting Increased Blood Sugar Levels in Type 2 Diabetes Mellitus Patients at Anshari Saleh Hospital Banjarmasin - Rahayu, Miranti; Ilmi, Bahrul; Solikin, Solikin; Syafwani, M; Ruslinawati, Ruslinawati (CV. Rayyan Dwi Bharata, 2025)
Degenerative diseases are non-communicable diseases (NCDs) that are chronic. According to WHO, there are four main types of NCDs, namely cardiovascular disease (coronary heart disease and stroke), cancer, chronic respiratory disease (asthma and COPD), diabetes mellitus. The high rate of increase in blood sugar levels of more than 200 mg/dl in diabetes mellitus patients is caused by many factors that cause an increase in blood sugar levels. The aim of this study was to analyze the factors that influence the increase in blood sugar levels in type 2 diabetes mellitus patients at Anshari Saleh Hospital, Banjarmasin. The design in this study used a cross sectional method. The statistical tests used are the Sperm Rank test and multiple logistic regression test. The sampling technique uses proportional sampling. The research results showed that there was an influence of physical activity, stress, emotional intelligence, eating patterns, and medication adherence with increasing blood sugar levels in diabetes mellitus patients (p0.05), there was no influence of obesity and heredity with increasing blood sugar levels in diabetes patients. Mellitus (p0.05) and the factor that has the most influence on increasing blood sugar levels in diabetes mellitus patients is diet with an odds ratio of 38,428. Nurses need to improve the quality of services by improving methods, educational media, or ways of conveying information that will be given to patients' families and patients regarding diabetes mellitus so that it is easier for families to understand.